Os desafios para o uso do planejamento estratégico nas organizações públicas: uma visão de especialistas - Ota, Eric Tatsuya (2014)
The purpose of this research was to study the challenges to the use of strategic planning in public organizations, from the point of view of specialist of the subject. Based on the literature of strategic planning and public administration was sought the theoretical framework of the limitations and barriers to the use of strategic planning in public organizations. The data were collected from interviews with public managers, who have worked directly with strategic planning in their public organization, and also, interviews with specialists in public management (academics and public management consulters). As a result of this analysis were indentified five dimensions that grouped the challenges to the use of strategic planning in public organizations: (1) Ensure engagement and commitment from all the people involved with the strategic planning; (2) Understand that the decision process must consider different perceptions and expectations; (3) Have flexibility to deal with political factors and turnovers; (4) Have sensibility with the organization culture and the principles of the public administration; (5) Understand the dynamic of the provision of human and financial resources at the public organizations.